Exploring Cultural Authority: The Dichotomies of Zikir Songs in the Malay Community of West Kalimantan - Ansari, Isa; Fauziyah, Nur; Pujiono, Bagong; Bugov, Dobrin Tsvetanov; Puspitasari, Elis (Institut Seni Indonesia Yogyakarta, 2025)
This article examines the reproduction of cultural authority within the Sambas Malay culture, emphasizing the distinctions in the utilization of songs for performing dhikr or barzanji in broader terms. This issue is approached through a multidisciplinary lens that integrates aspects of cultural studies, ethnomusicology, and symbolic capital. This research is qualitative because it explores the complex relationship between the dhikr practices of the community, resulting in narrative data. The data was collected through interviews and participant observation, which included engaging with the dhikr participants during their rituals and practices. The process of data analysis occurs in three distinct stages. Initially, data reduction is conducted to arrange the data in a more structured manner. The second point presents the reduced data thematically in a table that includes images, text quotes, and snippets of dialogue. Data verification was conducted to reach conclusions. The process of interpretation involved restating and reflecting on the data in light of the prevailing socio-cultural context. The findings suggest that the dichotomy acts as a means for dhikr practitioners to recreate cultural authority, aiming to reshape the Sambas Palace's influence over those who engage with traditional songs. This reproductive process occurs through inversion and reinforcement.